Women’s Perceived Likelihood to Engage in Sexual Risk Taking: Posttraumatic Stress Symptoms and Poor Behavioral Regulation - Hahn, Christine K. (Journal of interpersonal violence, 2021)
Sexual abuse prior to age 18 may put some women at risk for engaging in sexual risk taking. This association could exist, in part, as a result of the impact of posttraumatic stress symptoms on behavioral regulation. The current study utilized a path analysis to investigate the association between severity of sexual abuse before age 18, posttraumatic stress symptoms, poor behavioral regulation, and expected engagement in sexual risk taking among college women. The sample consisted of 88 college women with experiences of sexual abuse prior to the age of 18. Severity of sexual abuse predicted posttraumatic stress symptoms. In addition, posttraumatic stress symptoms predicted poor behavioral regulation, which in turn predicted expected engagement in sexual risk taking. These findings indicate functional mechanisms involved in sexual decision making of women who have had past sexual abuse and experience posttraumatic stress symptoms.